Exergy analysis of conjugate heat transfer through a building block with multiple enclosed spaces. (27th January 2010) - Antar, Mohamed A.
Exergy destruction due to heat transfer across a building block with multiple cavities is evaluated. Conduction heat transfer is considered within the solid material whereas both natural convection and Graybody radiation occur simultaneously in the air-filled cavities. The number of cavities was increased keeping the total width unchanged to investigate its effect on the heat transfer rate and exergy destruction. Using more cavities with less width provides better thermal insulation. In addition, it results in less exergy destruction. Exergy destruction and heat transfer rate can be further reduced by changing the cavities layout and the radiation properties of the block cavity surfaces.